COVID-19 vaccination and cerebral small vessel disease progression—A prospective cohort study - Yiu Ming Bonaventure Ip; Sangqi Pang; Alan Yao; Lucas Lau; Anki Miu; Katarina Chiu; Ho Ko; Andrew Kwok; Helen Y Chan; Sharon Lee; Howard Chan; Trista Hung; et al. (International Journal of Infectious Diseases)
Objectives: The association between SARS-CoV-2 spike protein and cerebrovascular diseases raised a concern of cerebrovascular safety of COVID-19 vaccines. We aimed to determine the risk of radiologic cerebral small vessel disease (cSVD) progression with BNT162b2 and CoronaVac. Methods: In this community-based prospective cohort study, community-dwelling subjects underwent brain magnetic resonance imaging (MRI) before and 4 months after vaccination with BNT162b2 or CoronaVac. Unvaccinated subjects received serial brain MRI over a comparable interval. The primary outcome was progression of a composite of six standard cSVD biomarkers. We compared the risk of cSVD progression between vaccinated and unvaccinated subjects and identified predictors of primary outcome within each vaccine subgroup. Results: Of the 415 subjects recruited, 190 received BNT162b2, 152 received CoronaVac, and 73 remained unvaccinated. A total of 60 (14.4%) had COVID-19 infection before follow-up MRI, and 109 (26.3%) developed the primary outcome. Neither BNT162b2 (adjusted odds ratio [aOR] 0.61, 95% confidence interval [CI] 0.30-1.26, P = 0.179) nor CoronaVac (aOR 0.71, 95% CI 0.34-1.47, P = 0.349) was associated with cSVD progression. Among the BNT162b2 recipients, a higher surrogate virus neutralization test was associated (aOR 0.97, 95% CI 0.95-0.99, P = 0.002) with a lower risk of cSVD progression. Conclusions: BNT162b2 and CoronaVac did not increase cSVD burden in community-dwelling citizens. The association between surrogate virus neutralization test and cSVD progression among BNT162b2 recipients requires further investigation.